Learning and behavior - Mazur, James E. (Pearson/Prentice Hall, 2006)
Mazur (Southern Connecticut State U.) presents an introductory textbook on the psychological aspects of how animals and humans learn and how their behavior is affected. He compares behavioral and cognitive approaches toward learning, theories, physiological elements, innate behavior and habituation, classical and operant conditioning, positive and negative reinforcement, avoidance and punishment, stimulus control and concept formation, comparative cognition, observational and motor-skills learning, and choice. The new edition has been reformatted and contains quizzes for each chapter